DEVERBALISATION OF -ATION AND DEADJECTIVALISATION OF -NESS IN ENGLISH: A COGNITIVE SEMANTICS PERSPECTIVE - Ayyuhatsanail Fithri (Journal of Language and Literature, 2026)
This paper examines the English nominalising suffixes -ation and -ness from a cognitive semantic perspective, focusing on the processes of deverbalisation and deadjectivalisation. The study investigates these two abstract noun-forming suffixes as its primary objects of analysis and employs a descriptive-explanatory method to interpret the research data. Particular attention is given to how -ation and -ness interact with lexical and conceptual meaning in the formation of abstract nouns. From a semantic standpoint, nouns derived with -ation typically express complex eventive or processual meanings, often involving argument structure and telicity that depend on the semantic properties of the verbal base. In contrast, -ness generally forms nouns that denote qualities or states abstracted from adjectival bases, exhibiting relatively stable semantic interpretations. The analysis is supported by corpus-based evidence and semantic classification frameworks that differentiate eventive from non-eventive interpretations of derived nominals. In addition, the study draws on theoretical insights from lexical semantics and frame semantics to explain the semantic behaviour of these derivational patterns. The findings indicate that both suffixes demonstrate productive derivational processes associated with polysemy and morphological productivity, with their semantic outcomes influenced by the grammatical category of the base and patterns of language use. Finally, the paper situates these findings within broader discussions of English nominal semantics and word formation, highlighting their implications for understanding the lexical-semantic representation of derived words.